2004
DOI: 10.1017/s0033291703008821
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of insight, paranoia and depression during early schizophrenia

Abstract: In first-episode psychosis, good insight predicts depression. Subsequently, paranoia is the strongest predictor. Neither effect is mediated by low self-esteem. Effective treatment of positive symptoms is important in preventing and treating low mood in early schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
109
2
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(133 citation statements)
references
References 31 publications
12
109
2
10
Order By: Relevance
“…Drake et al (2004) found that significant associations between depression and paranoia in a first episode psychosis sample would not fit a statistical model of mediation by self esteem. Other investigators have emphasised, instead of the balance of self esteem, specific negative beliefs about the self and about others, such as "I am vulnerable" or "others are hostile" as strongly connected to paranoia .…”
Section: Paranoia As a Defence Against Negative Self-evaluationsmentioning
confidence: 89%
See 3 more Smart Citations
“…Drake et al (2004) found that significant associations between depression and paranoia in a first episode psychosis sample would not fit a statistical model of mediation by self esteem. Other investigators have emphasised, instead of the balance of self esteem, specific negative beliefs about the self and about others, such as "I am vulnerable" or "others are hostile" as strongly connected to paranoia .…”
Section: Paranoia As a Defence Against Negative Self-evaluationsmentioning
confidence: 89%
“…Notably, all four studies that measured persecutory or delusional ideation specifically found that depression at a given time point was related to more severe subsequent paranoia (Drake et al, 2004;Fowler et al, 2011;Thewissen et al, 2011) or delusions (Bergstein, Weizman, & Solomon, 2008).…”
Section: Observational Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the absence of an association between depressive symptoms and insight is rather surprising in light of other findings in the literature [16,33,34,38,44]. Depression was hypothesized and several times proved to be in a positive relation with insight based on different theories, as summarized by Mutsatsa et al [35].…”
Section: Discussionmentioning
confidence: 97%